Engaging stimulatory immune checkpoint interactions in the tumour immune microenvironment of primary liver cancers – how to push the gas after having released the brake - Rakké, Yannick S.; Buschow, Sonja I.; IJzermans, Jan N. M.; Sprengers, Dave (Frontiers in Immunology, 2024)
Hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCA) are the first and second most common primary liver cancer (PLC). For decades, systemic therapies consisting of tyrosine kinase inhibitors (TKIs) or chemotherapy have formed the cornerstone of treating advanced-stage HCC and CCA, respectively. More recently, immunotherapy using immune checkpoint inhibition (ICI) has shown anti-tumour reactivity in some patients. The combination regimen of anti-PD-L1 and anti-VEGF antibodies has been approved as new first-line treatment of advanced-stage HCC. Furthermore, gemcibatine plus cisplatin (GEMCIS) with an anti-PD-L1 antibody is awaiting global approval for the treatment of advanced-stage CCA. As effective anti-tumour reactivity using ICI is achieved in a minor subset of both HCC and CCA patients only, alternative immune strategies to sensitize the tumour microenvironment of PLC are waited for. Here we discuss immune checkpoint stimulation (ICS) as additional tool to enhance anti-tumour reactivity. Up-to-date information on the clinical application of ICS in onco-immunology is provided. This review provides a rationale of the application of next-generation ICS either alone or in combination regimen to potentially enhance anti-tumour reactivity in PLC patients.